Performance Potential and Limit of MoS2 Transistors. (13th January 2015) - Li, Xuefei; Yang, Lingming; Si, Mengwei; Li, Sichao; Huang, Mingqiang; Ye, Peide; Wu, Yanqing
<x xml:space="preserve">Abstract</x> High‐performance MoS2 transistors scaled down to 100 nm are studied at various temperatures down to 20 K, where a highest drive current of 800 μA μm−1 can be achieved. Extremely low electrical noise of 2.8 × 10−10 μm2 Hz−1 at 10 Hz is also achieved at room temperature. Furthermore, a negative differential resistance behavior is experimentally observed and its origin of self‐heating is identified using pulsed‐current–voltage measurements. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>